2010
DOI: 10.1001/archophthalmol.2010.221
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Stem Cell Populations in Preterm Infants

Abstract: To investigate the association among different circulating stem cell (SC) populations, the levels of selected growth factors and chemokines regulating SC migration in the peripheral blood, and the incidence of retinopathy of prematurity (ROP). Methods: We evaluated 88 participants in this study: 29 preterm infants with ROP, 29 preterm infants without ROP, and 30 healthy full-term infants. Peripheral blood samples collected 10 weeks after delivery were analyzed using flow cytometry, immunofluorescence, realtime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…To analyze distinct stem cell types we selected CD45 - lin - CD184 + and CD45 + lin - CD184 + phenotypes that represent primitive, non-hematopoietic (non-HSC) and hematopoietic (HSC) stem cells, respectively [5,6,17]. Based on our previous reports, and in order to verify whether or not the population of non-HSCs comprise very small embryonic-like stem cells (VSELs), thus we evaluated in parallel the expression of markers common to pluripotent or undifferentiated cells by immunocytofluorescence and qRT-PCR in those cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze distinct stem cell types we selected CD45 - lin - CD184 + and CD45 + lin - CD184 + phenotypes that represent primitive, non-hematopoietic (non-HSC) and hematopoietic (HSC) stem cells, respectively [5,6,17]. Based on our previous reports, and in order to verify whether or not the population of non-HSCs comprise very small embryonic-like stem cells (VSELs), thus we evaluated in parallel the expression of markers common to pluripotent or undifferentiated cells by immunocytofluorescence and qRT-PCR in those cells.…”
Section: Resultsmentioning
confidence: 99%
“…Receptor CXCR4 (CD184) plays an important role in the mechanisms of HSCs migration and repopulation, in regard to the observation, that murine fetuses lacking this receptor (CXCR4-null model) have multiple defects that are lethal, including impaired BM hematopoiesis [28]. Recently, we were able, not only to confirm the presence of such highly restrictive SCs populations among blood leukocytes, but also to quantitatively determine the absolute numbers of these infrequent cells circulating in the blood of patients with various tissue/organ injuries and disorders [5,6,17]. Of note, the defined CD45 – lin – CD184 + and CD45 + lin – CD184 + SC populations have not been previously evaluated in relatively long-term prospective observation in PB of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously found higher early-and late-EPC counts in umbilical cord blood (UCB) of premature infants compared with full-term neonates [19]. Furthermore, we also reported that elevated numbers of early endothelial progenitor cells in the peripheral blood of preterm neonates were associated with retinal injury [20]. Machalinska et al has also found that in preterm neonates with hypoxic retinopathy, elevated VEGF and IGF-1 blood levels correlated with retinal abnormalities, indicating that these trophic factors may be predictive of abnormal neurodevelopmental outcomes, including retina [21].…”
Section: Introductionmentioning
confidence: 86%